Contribution Of Seafloor Research To Land-Based VMS Exploration - Gérald Riverin (International Marine Minerals Society, 1998)
Over the past century, exploration methods for volcanogenic massive sulphide deposits have evolved in response to a decreasing number of discoveries made by traditional surface prospecting and by ground and airborne geophysics. Statistical trends support the concept that fewer and fewer outcropping and sub-cropping VMS discoveries will be made in the future. In turn, this creates new opportunities to develop more sophisticated exploration models and techniques to explore at greater depth and to make blind discoveries. Current exploration models include various combinations of geological, geochemical and geophysical criteria which have been based on the results of land-based VMS research. The role of seafloor research in the development of these models has so far been only of a subordinate nature, perhaps due to a lack of direct involvment of the exploration industry in the seafloor research, and vice-versa for the seafloor researchers in VMS exploration. Another contributing factor is that exploration relies on exploration criteria that result from detailed geological, geochemical and geophysical studies of both footwall and hanging wall rocks, studies that are not possible in modern sea floor environments. Nevertheless, seafoor research has contributed to our understanding of the growth of sulphide mounds, the mechanism of sulphide deposition and of the chemistry of fluids involved in VMS systems. In particular, the role of structure and of tectonic setting has been clarified through observation of active seafloor hydrothermal systems. In turn, observations made in land-based VMS research has helped seafloor researchers to focus on key issues which, will eventually contribute to improved exploration models.